npj Acoustics - Horoshenkov, Kirill; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Acoustics considers research relating to the discipline of acoustics. Important areas of interest are the generation, propagation, sensing, manipulation, and perception of sound and the analysis of related acoustic phenomena. The journal covers a broad range of topics including but not limited to: Acoustic materials such as metamaterials, porous media, and smart structures for sound manipulation Transducers for sound generation and sensing Acoustic signal processing Hearing, audiology, and medical acoustics Psychoacoustics, perception of sounds by biological species, and noise effects Musical acoustics, immersive audio, and soundscapes Theoretical understanding of the basic science of acoustics (infrasound, audible sound waves, and ultrasonics) Computational methods for predicting acoustic wave phenomena The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by acoustics experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals. .
Keywords: Acoustical engineering; Acoustics; Mechanics, Applied; Science$1 (BSocial aspects.s; Environmental engineering; Civil engineering; Materials$1 (BAnalysis.s; Imaging systems; Engineering Acoustics; Acoustics; Engineering Mechanics; Sound Studies; Environmental Civil Engineering; Imaging Techniques